Comparison of bilateral differential characteristics of corneal biomechanics between keratoconus and normal eyes - Xian, Yiyong; Zhao, Yu; Sun, Ling; Zhang, Xiaoyu; Ding, Lan; Liu, Zesheng; Li, Yuan; Ding, Yanlan; Jiang, Lin; Zhou, Xingtao; Shen, Yang (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: To compare bilateral differences in corneal biomechanics between keratoconus and normal eyes. Methods: In this case-control study, 346 eyes of 173 patients (aged 22.1 ± 6.1 years) with keratoconus (KC group) and 378 eyes of 189 patients (aged 26.7 ± 5.6 years) with ametropia (control group) were enrolled. Corneal tomography and biomechanical properties were examined using Pentacam HR and Corvis ST, respectively. The corneal biomechanical parameters were compared between eyes with forme fruste keratoconus (FFKC) and normal eyes. Bilateral differences in corneal biomechanical parameters were compared between the KC and control groups. Receiver operating characteristic (ROC) analysis was used to assess discriminative efficacies. Results: The areas under the ROC curves (AUROCs) of stiffness parameter at the first applanation (SP-A1) and Tomographic and Biomechanical Index (TBI) for identifying FFKC were 0.641 and 0.694, respectively. The bilateral differential values of major corneal biomechanical parameters were significantly increased in the KC group (all p < 0.05), except for the Corvis Biomechanical Index (CBI). The AUROCs of the bilateral differential values of the deformation amplitude ratio at 2 mm (ΔDAR2), Integrated Radius (ΔIR), SP-A1 (ΔSP-A1), and the maximum inverse concave radius (ΔMax ICR) for discriminating keratoconus were 0.889, 0.884, 0.826, and 0.805, respectively. The Logistic Regression Model-1 (comprising of ΔDAR2, ΔIR, and age) and the Logistic Regression Model-2 (comprising of ΔIR, ΔARTh, ΔBAD-D, and age) had AUROCs of 0.922 and 0.998, respectively, for discriminating keratoconus. Conclusion: The bilateral asymmetry of corneal biomechanics was significantly increased in keratoconus compared with normal eyes, which may be helpful for the early detection of keratoconus.